Assessment of antiurolithiatic potential of gallic acid on calcium oxalate crystallization and ethylene glycol induced lithiasis - Patel, Neeraj Kumar; Basedia, Deepak Kumar; Dubey, B. K. (Asian Journal of Pharmaceutical Research and Development, 2021)
In the present work, the effect of gallic acid on nucleation and aggregation of calcium oxalate crystals and on ethylene glycol induced lithiasis was evaluated. Gallic acid is a natural phenolic compound found in several fruits and medicinal plants. It is reported to have several health-promoting effects. The presence of peaks at 3700, 1715, 1550-1650 are indicative of the presence of hydroxyl, carbonyl, and aromatic ring respectively. The results of solubility analysis indicate that gallic acid is soluble in organic solvents easily and is partially or sparingly soluble in aqueous solution. Gallic acid was able to inhibit the rate of nucleation as well as aggregation of calcium oxalate crystals in the in vitro experiment. It is exerted diuretic action in rats and was able to decrease the activity of the biomarkers of lithiasis viz. lactate dehydrogenase and alkaline phosphatase in ethylene glycol induced lithiatic rats. It could be concluded from the study that gallic acid is a potent anti urolithiatic compound and can be optimized for treatment of kidney stones.